Estimation of the Adaptive Capacities of the Cardiovascular System in Pregnant Females by Active Orthostatic Test - Yu. V. Struk; N. V. Shapovalova; N. Yu. Denisova (Общая реаниматология)
The investigation was undertaken to study the adaptive capacities of the cardiovascular system (CVS) in physiological full-term pregnancy, by using the active orthostatic test (AOT) and to analyze cardiac rhythm variability (CRV). The study covered 49 low-risk group females during 38—39-week physiological pregnancy, who had indications for planned surgery -cesarean section. Before surgery, during an anesthesiological examination, all the pregnant females performed AOT during which ECG was continuously recorded. For CRV estimation, 5-min ECG fragments recorded in the standing and lying positions. AOT could reveal a normal orthostatic response (NOR) in 37 pregnant females, postural orthostatic tachycardia (POT) in 8 and orthostatic hypotension in 4. No relationship was found between the clinical characteristics and the types of responses to AOT. At the same time, comparison of CVS demonstrated that the baseline enhanced activity of the sympathetic portion of the autonomic nervous system was typical of females with POT as compared with females showing a NOR. Thus, estimation of CRV parameters in pregnant females permits predetermination of adaptive CVS capacities, which is important to be taken into account in choosing an anesthesiological support and modes of hemodynamic correction when cesarean section is performed.